Incorporating Linguistic Landscape (LL) for Developing ESL/EFL Learners’ Linguistics Critical Literacy Competence: A critical literature review - Yulius Yosef Kasimo (Program Studi Pendidikan Bahasa Inggris, 2023)
This aimed at investigating and analyzing the significance of incorporating linguistic landscape (LL) into the process of acquiring/leaning English as Second Language (ESL), or Foreign Language (EFL) and finding the approaches and tehniques of integrating linguistic landscape into that processes. Through the critical literature review method, this study was conducted through searching, reading, categorizing, analyzing, evaluating and synthesizing the previous studies combined with other relevant sources. Thus, this study documented two benefits findings. 1) Linguistic landscape helps ESL/EFL learners to advance their comprehension of linguistic critical literacy that includes sociolinguistics, morphological formation, semantics, pragmatics, and semiotics. 2) Experiential learning, situated learning, community-based learning and project-based learning are the effective and efficient approaches that must be applied to integrate linguistic landscape into the teaching and learning English as second language/foreign language.